CHILD VISITATIONS WITH FATHERS SERVING A PRISON SENTENCE - Aneta Jarzębińska (Probacja)
Contact with the children of a parent who is serving a prison sentence can be associated with significant benefits. The potential benefits involve the convicted parent. They can be immediate, as well as achieved in the long term, and one of the most important is that the parent refrains from violating the legal norm in order to maintain a good relationship with the child. A child can benefit from contact with an incarcerated parent, although not unconditionally and with exceptions. This contact can also be valuable to the other parent and even to the prison unit. Despite the potential attributed to it, contacts of inmates with family members, including their special form – visitations – are issues poorly recognized by researchers in Poland. The main goal of the article is to contribute to bridging this gap in knowledge by presenting the results of own research.The overall goal of the own research was to determine the place of visitations in the structure of incarcerated fathers' contact with their children. The material for the study came from the author's questionnaire filled out by 159 fathers serving a prison sentence in one of four prisons in Poland. After analysing the information from the completed questionnaires, it was found that 2/3 of the men had contact with their child/children while in prison. Most fathers maintained contact in the form of phone calls, fewer in the form of visits, and the least corresponded with their child. It was found that inmates were visited by less than half of the children they declared having, and that among fathers visited by their child, the largest proportion were those whose child visited as often as allowed by law.It was discovered that there are correlations between fathers' socio-demographic characteristics such as marital status, age, level of education, length of sentence, length of incarceration and number of stays in prison and whether they had child visitations. The highest percentage of fathers visited by their child was recorded among married fathers, those classified in the oldest age group adopted in the study, those with a high school education, those serving a long-term sentence, those serving their current sentence having spent no more than three years in prison, and those in prison isolation for the first time.